The crisis of the human sciences : false objectivity and the decline of creativity - Botz-Bornstein, Thorsten; Botz-Bornstein, Thorsten (Cambridge Scholars Publishing, 2011)
Centralization and over-professionalization can lead to the disappearance of a critical environment capable of linking the discipline to the real world. The authors of this volume suggest that humanities need to operate in a concrete cultural environment able to influence procedures on a hic et nunc basis and should not entirely depend on normative criteria whose function is often to hide ignorance behind a pretentious veil of value-neutral objectivity. In sociology the growth of scientism has fragmented ethical categories and distorted discourse between inner and outer selves, while philosophy is suffering from an empty professionalism current in many philosophy departments in industrialized and developing countries where boring, ahistorical, and nonpolitical exercises are justified through appeals to false excellence. In all branches of the humanities absurd evaluation processes foster similar tendencies as they create a sterile atmosphere and prevent interdisciplinarity and creativity. Technicization of theory plays into the hands of technocrats. The authors offer a broad range of approaches and interpretations reaching from philosophy of education to the reevaluation of business models for the university.